Continuous monitoring of intravascular volume status during renal replacement therapy in the critically ills using plethysmography variability - How, Ang Chee (2018)
Background: Intravascular volume status monitoring in the critical care setting remains a big challenge to intensive care providers especially in the groups of patients who receives renal replacement therapy despite the abundance of choices available to assist physicians. This pilot study aims to investigate the degree of agreement of plethysmographic variability index (PVI) of two different sites(digits and forehead) with a) dynamic modality of pulse pressure variation (PPV) and intraarterial blood pressure (IABP) and b) static modality of central venous pressure measurement(CVP) in the assessment intravascular volume status in critically ill patients who requires renal replacement therapy. Methods: This was a prospective observational comparative study conducted in 2 phases (phase 1- pilot study, phase 2 -continuous study). A total of 30 patients (phase 1- 10, phase 2- 20) who were admitted to critical care facilities, intubated and prescribed with renal replacement therapy and fulfilled study criteria were recruited in this study after consented by the legal guardian. The PVI (digit and forehead), CVP, PPV, and intra-arterial blood pressure(IABP) values were collected at an interval of 5 minutes 30 minutes pre-dialysis and at an interval of 30 minutes till completion of dialysis. Categorical variables were expressed in frequency and percentage with 95% confidence interval while numerical variables were expressed in mean and standard deviation. Agreement analysis between set of data was doneusing the Cohen’s Kappa analysis. P value of < 0.05 is considered statistically significant. All data were analysed using SPSS version 22.0. Results: A total of 250 sets of data were obtained from 20 study subjects from phase 2. The mean age for patients included this study was 60 ± 9. There were 70% male and 30% female. The mean APACHE score of the participants was 25.8±10.0. PVI showed statistically almost perfect agreement between measurements from digits and forehead(r= 0.98, CI= 95% 0.98±0.01, p<0.01). PVI was shown to have a fair agreement with CVP (digit: r= 0.27, CI= 95% 0.27±0.11, p<0.01 forehead: r= 0.27, CI= 95% 0.27±0.11, p<0.01) as well as MAP (digit: r =0.22, CI= 95% 0.22±0.11, p<0.01 forehead: r=0.21, CI= 95% 0.21±0.10, p<0.01). However, PVI shows moderate agreement with PPV (digit: r= 0.56, CI= 95% 0.56±0.09 , p<0.01forehead: r= 0.53, CI= 95% 0.53±0.09, p<0.01). Conclusion: This study demonstrates almost perfect agreement of PVI taken at digits and forehead, a moderate agreement between PVI and PPV and a fair agreement between PVI, CVP and MAP.